PENINGKATAN KAPASITAS PETANI DAN PETERNAK DALAM PENGELOLAAN KEUANGAN DAN ADMINISTRASI USAHA AGRIBISNIS DI DESA WARNASARI, PANGALENGAN JAWA BARAT - Patiandari, Patiandari; Rianto, Rianto; Efrinal, Efrinal; Kurniawan, Elan; Abdurrosyid, Moh. (POLITEKNIK LP3I JAKARTA, 2025)
This community service program was implemented with the aim of increasing the capacity of farmers and livestock breeders in Warnasari Village, Pangalengan District, West Java in terms of financial management and business administration. The main problem faced by the local community is the lack of understanding of simple financial records and effective and sustainable business management. This activity is important considering the village's great potential in the fields of agriculture and livestock which has not been balanced with a good business management system. The method of implementing the activity includes training, direct assistance, and simulation of daily and monthly financial records. Participants are trained to make simple financial reports, prepare business budget plans, and understand the importance of recording transactions in making business decisions. In addition, the implementation team also provides easy-to-understand training modules so that participants can continue to learn independently. The results of this activity show an increase in participants' understanding and skills in preparing financial reports and managing their businesses in a more organized manner. Several farmers and livestock breeders have even started implementing a daily recording system and preparing short-term business plans. This program is expected to become a model for local economic empowerment based on increasing administrative and financial capacity in the agriculture and livestock sectors.